2009
DOI: 10.1089/ten.tea.2008.0666
|View full text |Cite
|
Sign up to set email alerts
|

Bone-Forming Capacity of Mesenchymal Stromal Cells When Cultured in the Presence of Human Platelet Lysate as Substitute for Fetal Bovine Serum

Abstract: In tissue engineering, strategies are being developed to repair large bone defects by combining biomaterials and bone marrow-derived multipotent mesenchymal stromal cells (MSCs). For expansion of MSCs under good manufacturing practice conditions, human platelet lysate (PL) can serve as substitute for fetal bovine serum (FBS) in culture media. We compared the in vivo bone-forming capacity of passage 3 MSCs cultured with either PL or FBS for nine different human donors. We also tested the growth kinetics, antige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
72
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 81 publications
(88 reference statements)
5
72
0
Order By: Relevance
“…Aiming to develop articular therapies by combining PRP and MSCs, Mishra et al 44 showed that buffered PRP enhanced the expression of chondrogenic markers, such as Sox9 and Aggrecan. These findings were corroborated in further studies 7,8,12,27,29,47 that showed enhanced chondrogenic differentiation, and extracellular cartilage matrix synthesis in the presence of PRP. Likewise, Shih et al 12 also proved that chondrogenic differentiation was enhanced and maintained through cell passages in PRP cultures comparing to FCS cultures.…”
Section: Cell Differentiationsupporting
confidence: 67%
“…Aiming to develop articular therapies by combining PRP and MSCs, Mishra et al 44 showed that buffered PRP enhanced the expression of chondrogenic markers, such as Sox9 and Aggrecan. These findings were corroborated in further studies 7,8,12,27,29,47 that showed enhanced chondrogenic differentiation, and extracellular cartilage matrix synthesis in the presence of PRP. Likewise, Shih et al 12 also proved that chondrogenic differentiation was enhanced and maintained through cell passages in PRP cultures comparing to FCS cultures.…”
Section: Cell Differentiationsupporting
confidence: 67%
“…An MTT assay was performed at indicated time points (24,48, 72 h and 1 week) in both standard and xeno-free conditions (Fig. 1F) to measure the viability and proliferation rate of each stem cell population.…”
Section: Cell Growthmentioning
confidence: 99%
“…21 Previous studies report that human platelet lysate and human plasma can replace FCS in terms of clinical-scale expansion 22,23 and in vivo bone-forming capacity of human mesenchymal stromal cells. 24 Human serum could be considered a suitable alternative, due to its possibility to promote osteogenic differentiation in DPSCs and to induce an efficient expansion of umbilical cord-derived stem cells, 25 but this approach could be limited by the amount of autologous serum necessary to expand MSCs for clinical use and the variability of serum, especially for patients receiving previous chemotherapy. 26 In any case, the elaboration of a culture medium, adaptable to the production of stem cells for the clinical application of cell therapy, remains a crucial matter, as a serum-free medium with no growth factors is unable to amplify these cells in vitro, and the type of serum used (FBS, human serum, and allogenic or autologous serum or plasma) is highly debated.…”
mentioning
confidence: 99%
“…34 It has been indicated that cells with a smaller cell size have a higher differentiation capacity. 35 The inability of hADSC to become confluent when cultured in FBS containing DMEM high glucose medium might be due to higher ROS production and thus could promote cell death. 36,37 On the other hand, hADSC that was cultured in platelet lysate containing DMEM high glucose or low glucose showed good results (data not shown).…”
Section: Discussionmentioning
confidence: 99%